Eight-point scheme proposal for translating the Qur'anic text - Alhalawani, Ali Alsayed Hassan (David Publishing Company, USA, 2016)
The purpose of this paper is to examine the issue of translating the Qur’anic text into foreign languages. In so doing, the paper considers the unique features and characteristics of the language of the Qur’an and the special difficulties encountered by translators, from many different backgrounds, of the divine text. Different types of translation in relation to the Qur’an —literal, non-literal, and interpretive—are briefly discussed. Based on this discussion, this paper proposes an eight-point scheme to best translate the meaning of the different Qur’anic terms and/or expressions. This scheme can be applied either by an individual translator or a body of translators alike. This paper shows that the language of the Qur’an poses considerable obstacles to the translators. Thus, the best mode of translation in relation to the Qur’an is the interpretive one. It also calls upon researchers and translators to examine the proposed eight-point scheme for validity, usefulness, and further development.